Caramel pecan roll murder eaudiobook - Fluke, Joanne (Hannah Swensen Mystery, 2022)
In this scrumptious cozy mystery from New York Times and USA Today bestselling author Joanne Fluke, baker Hannah Swensen is tempted by a highprofile tournament in Lake Eden that quickly turns deadly ... Embracing a sweet escape from her usual routine at The Cookie Jar, Hannah gets asked for her help in baking pastries at the local inn for a flashy fishing competition with big prizes and even bigger names. But the fun stops when she spots a runway boat on the water and, on board, the lifeless body of the event's renowned celebrity spokesperson ... Famed TV show host Sonny Bowman wasn't humble about his ability to reel in winning catches, and no one knew that better than his tragically overworked sidekick, Joey. Did Joey finally take bloody revenge on his pompous boss—or was Sonny killed by a jealous contestant? With goodies to bake and a mess of fresh challenges mixed into her personal life, it's either sink or swim as Hannah joins forces with her sister, Andrea, to catch a clever culprit before another unsuspecting victim goes belly up ... Features Over a Dozen Cookie and Dessert Recipes from The Cookie Jar!